Практичний аспект взаємозв’язку управлінського та податкового обліку - Гапоненко, Ольга Євгенівна (НТУ "ХПІ", 2015)
Статтю присвячено встановленню взаємозв’язку та розбіжностей управлінського та податкового обліку в сучасних умовах господарювання, а саме: проведено порівняльний аналіз управлінського та податкового обліку за основними ознаками, представлено їх співставлення в частині виникнення доходів і витрат відповідно до Положень (стандартів) бухгалтерського обліку та Податкового кодексу України, наведено перелік тимчасових та постійних податкових різниць, що існують при формуванні об’єкта оподаткування (фінансового результату); надано науково-методичні та практичні рекомендації щодо формування основних умов ведення управлінського та податкового обліку з метою посилення їх єдності та взаємозв’язку.

One of the most important conditions for increasing the efficiency of production is to maximize the completeness and accuracy of the information on the actual level of expenditures and tax payments, because the last determines competitive position of the company. The article is devoted to the linkages and differences between managerial and tax accounting in the modern business environment, namely: a comparative analysis of managerial and tax accounting on the main characteristics presented their comparison in terms of revenue and expenses according to the following criteria: the definition, the moment of recognition, the conditions of recognition and classification. Practical aspects of accounting the revenue and expenses of the enterprise are studied in the accounting system and for tax purposes. It is systematized on the examples the main differences in the formation of profit (the object of taxation) by the way of determination of permanent tax differences and temporary tax differences in accordance with the provisions of the Tax code of Ukraine and Provisions (standards) of accounting. These provisions reveal the relationship and differences between managerial and tax accounting and allow undertaking the main directions of their unification. Directions of scientific-methodical and practical recommendations are determined for establishing the conditions for the relationship management and tax accounting.
The practical aspect of the interaction of managerial and tax accounting
Keywords: система обліку; об’єкт оподаткування; податкова різниця; доходи; витрати; accounting; revenues; expenses; object of taxation; tax differences